A comparison of shared and distributed situation awareness in teams through the use of agent-based modelling. (2nd January 2016) - Kitchin, Joanne; Baber, Chris
ABSTRACT: The question of how situation awareness is managed in a team remains a challenge for ergonomics. In this paper, a task was designed in which team members were required to identify a 'rogue' vehicle in road traffic. In one version of the task, team members see the same information in the same format, and in the other version, team members each have a different view of the situation. Performance was less accurate in the second version of the task and this was not affected by communication between team members. An agent-based model was developed to reflect the performance of the teams in the experiment and to allow manipulation of team characteristics. The models showed that the 'expertise' of agents affects not only their performance on the task but also their communication. This suggests that such modelling could be a useful line of research for the study of situation awareness.